2002
DOI: 10.1038/sj.bjp.0704502
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 3,4‐methylenedioxymethamphetamine (MDMA, ?ecstasy?) and its metabolites on neurohypophysial hormone release from the isolated rat hypothalamus

Abstract: 9ZR1 Methylenedioxymethamphetamine (MDMA,`ecstasy'), widely used as a recreational drug, can produce hyponatraemia. The possibility that this could result from stimulation of vasopressin by MDMA or one of its metabolites has been investigated in vitro. 2 Release of both oxytocin and vasopressin from isolated hypothalami obtained from male Wistar rats was determined under basal conditions and following potassium (40 mM) stimulation. The results were compared with those obtained for basal and stimulated release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 34 publications
1
47
1
1
Order By: Relevance
“…Other useful avenues of enquiry could examine changes in the efficacy of 5-HT receptor subtypes, changes in the transcription of 5-HT-related receptors, and alterations of basal and stimulated 5-HT within the synapse. The ability of MDMA to alter endocrine function chronically (Forsling et al, 2002) is another avenue through which anxiety may be affected as well as global effects on brain energy metabolism (Darvesh et al, 2002). Thus, it would be premature to conclude that the present study has isolated the mechanism through which MDMA chronically increases anxiety in rats.…”
Section: Discussionmentioning
confidence: 75%
“…Other useful avenues of enquiry could examine changes in the efficacy of 5-HT receptor subtypes, changes in the transcription of 5-HT-related receptors, and alterations of basal and stimulated 5-HT within the synapse. The ability of MDMA to alter endocrine function chronically (Forsling et al, 2002) is another avenue through which anxiety may be affected as well as global effects on brain energy metabolism (Darvesh et al, 2002). Thus, it would be premature to conclude that the present study has isolated the mechanism through which MDMA chronically increases anxiety in rats.…”
Section: Discussionmentioning
confidence: 75%
“…Ecstasy is a potent inducer of the secretion of AVP (57)(58)(59)(60). Henry and colleagues demonstrated that small doses of MDMA (40 mg; common "street dose" is 100 mg) led to a significant increase in AVP levels (from 1.14-1.88 pmol/L to 2.46-9.16 pmol/L) within 1-2 hours after dosing.…”
Section: Clinical Manifestations Of Ecstasy Use and Underlying Pathogmentioning
confidence: 99%
“…MDMA administration stimulated ADH release from rat hypothalamus in vitro (26) and in healthy, normally hydrated human male volunteers, with a drop in serum sodium accompanying the rise in serum ADH (27). Additional evidence for MDMA-induced ADH secretion has been provided by determination of elevated levels of ADH in a patient with hyponatremic coma after Ecstasy ingestion (20).…”
Section: Discussionmentioning
confidence: 96%